Multiple ER‐to‐nucleus stress signaling pathways are activated during Plantago asiatica mosaic virus and Turnip mosaic virus infection in Arabidopsis thaliana. (25th June 2020) - Gayral, Mathieu; Arias Gaguancela, Omar; Vasquez, Evelyn; Herath, Venura; Flores, Francisco J.; Dickman, Martin B.; Verchot, Jeanmarie
SUMMARY: Pathogens and other adverse environmental conditions can trigger endoplasmic reticulum (ER) stress. ER stress signaling increases the expression of cytoprotective ER‐chaperones. The inositol‐requiring enzyme (IRE1) is one ER stress sensor that is activated to splice the bZIP60 mRNA that produces a truncated transcription factor that activates gene expression in the nucleus. The IRE1/bZIP60 pathway is associated with restricting potyvirus and potexvirus infection. This study shows that the Plantago asiatica mosaic virus (PlAMV) triple gene block 3 (TGB3) and the Turnip mosaic virus (TuMV) 6K2 proteins activate alternative transcription pathways involving the bZIP17, bZIP28, BAG7, NAC089 and NAC103 factors in Arabidopsis thaliana . Using the corresponding knockout mutant lines, we show that bZIP17, bZIP60, BAG7 and NAC089 are factors in reducing PlAMV infection, whereas bZIP28 and bZIP60 are factors in reducing TuMV infection. We propose a model in which bZIP60 and bZIP17 synergistically induce genes restricting PlAMV infection, while bZIP60 and bZIP28 independently induce genes supporting PlAMV infection. Regarding TuMV‐green fluorescent protein (GFP) infection, bZIP60 and bZIP28 serve to repress local and systemic infection. Finally, tauroursodeoxycholic acid treatments were used to demonstrate that the protein folding capacity significantly influences PlAMV accumulation. Significance Statement: The IRE1/bZIP60 pathway of unfolded protein response responds to potyviruses and potexviruses to limit infection. This study reveals that additional endoplasmic reticulum (ER)‐to‐nucleus signaling pathways are activated by the Plantago asiatica mosaic virus and the Turnip mosaic virus, and restrict virus accumulation by increasing the protein folding capacity of the ER.